Coping: Impact of Gender and Stressful Life Events in Middle and in Old Age. Issue 5 (19th October 2016) - Rubio, Laura; Dumitrache, Cristina; Cordon-Pozo, Eulogio; Rubio-Herrera, Ramona
ABSTRACT: Objectives: This study seeks to identify different life events that participants considered stressful and to study the joint effect of gender, age group, and main stressful life events on the use of different coping strategies.Methods: The sample comprised 243 men and women, 55 to 99 years old, who attended senior activity centers. Analyses were conducted using multivariate analysis of variance (MANOVA).Results: Three main categories of stressful life events were identified: health problems, family problems, and other problems. Significant main effects of gender and stressful life events, and marginal effects of age group on coping strategies were found. Furthermore, an interaction between gender and age group, and also between gender and stressful life events emerged in some of the coping strategies analyzed.Conclusions: Age, gender or type of stressful situation impact on the coping strategies used by older people. Older men and women were found to use different strategies depending upon the situation they are facing and upon their age group. The results may prove useful to practitioners and clinicians who directly work with older people and may help clinicians provide effective coping strategies to address the specific life events that older adults find stressful.